The effect of ashwagandhadi granules on physical performance in healthy individuals - N K Ashitha; Bargale Sushant Sukumar (Wolters Kluwer Medknow Publications, 2022)
Introduction: Physical fitness is a state of health and well-being and more specifically, the ability to perform the aspects of sports, occupations, and daily activities. A higher fitness level indicates a better long-term effect of health. Physical fitness is generally achieved through a proper nutrition, moderate physical exercise, hygiene, and sufficient rest. Considering the nutritional aspect of physical fitness, supplements are required to bridge the nutritional gap due to busy work schedule and faulty food habits. Hence, a health supplement is the need for the hour which is tasty, will meet the daily requirements, and provide optimum nutrients for improving the physical fitness. Materials and Methods: Ashwagandhadi granules, formulated with a combination of food and Rasayana dravyas, consisting of Ashwagandha (Withania somnifera), Shatavari (Asparagus racemosus), Ragi (Eleusine coracana), Mudga (Vigna radiata), Jeeraka (E. coracana), and Shunti (Zingiber officinale), can be a promising health supplement. An open-label double-arm control clinical study with convenient sampling and modified wait-listed crossover design was conducted among 23 individuals. While in the study group, they were administered with 20 g of Ashwagandhadi granules with 150 ml milk for a month. Results: The result revealed a statistically significant change in the Harvard Step Score and VO2 max (z = 3.83, P < 0.001). Conclusion: The administration of Ashwagandhadi granules has a statistically significant effect on physical fitness.